2015
DOI: 10.1007/s10995-015-1808-9
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Care Admissions in Pregnancy: Analysis of a Level of Support Scoring System

Abstract: In a cohort of women requiring intensive care admission during pregnancy, MCCWG LOC, a simplified organ system based, triaging scoring system, predicted maternal outcomes and correlated with APACHE II score. Our data support initiatives for further development and testing of global obstetric triaging scoring systems for the purposes of risk stratification, monitoring of quality and resource allocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…It has been seen that an early and elective transfer of patients to the ICU by identifying the risk factors can help us in achieving the goal of decreasing maternal mortality. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…It has been seen that an early and elective transfer of patients to the ICU by identifying the risk factors can help us in achieving the goal of decreasing maternal mortality. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…An additional 11 articles were identified through the reference lists and citation tracking of 316 relevant articles with use of Web of Science. Finally, 38 studies of 12 prediction models met inclusion criteria (Tables 1 and 2, Figs 3 and 4, and S1 Table) [4,17,36–45,28,4655,29,56–63,3035]. The TRIPOD checklist of all 38 eligible articles is available on request (S2 File).…”
Section: Resultsmentioning
confidence: 99%
“… 11 However, Vasquez et al and Thakur et al have reported higher incidences of nonobstetric ICU admissions in their study. 12 , 13 Interestingly, women admitted for nonobstetric causes may have higher disease severity scores on admission and a higher need for mechanical ventilation and other ICU interventions. 11 , 14 16 Table 1 lists the obstetric and nonobstetric causes of ICU admissions by various authors in the last decade.…”
Section: Ethodsmentioning
confidence: 99%
“…However, it was observed that the general scores were not able to accurately predict the outcomes of pregnant women in the critical care due to the physiological changes in pregnancy which have a bearing on the variables of these models; another reason being that many critical conditions improved remarkably after delivery of the fetus and placenta, leading to over prediction of mortality by the general scores. 12 , 13 , 16 , 18 24 Thus, the need for customization of the scores for obstetric patients was perceived. This led to development of specific ObPMs.…”
Section: Ethodsmentioning
confidence: 99%